A critical reflection on eportfolio as a teaching tool - Lyn Lewis (New Zealand Journal of Teachers' Work)
Eportfolios are used in early childhood, primary, secondary and higher education settings in New Zealand. While it is common practice to use the tool functions for the storage and presentation of learning, the use of eportfolio as a pedagogy is less well established. This article focuses on the author’s use of the Mahara eportfolio with primary students in an initial teacher education programme. Four critical reflective lenses are used to explore eportfolio in three learning activities: developing metacognitive skills through standards-based activities; journalling for attitudinal awareness; and expressing learning through visual narrative in an eposter. An argument is made for a shift in focus from eportfolio as a tool, towards its pedagogical capabilities. While the context of practice is higher education, the eportfolio pedagogies can be transferred to early childhood, primary or secondary contexts.